Continuous peritoneal dialysis compared with daily hemodialysis in patients with acute kidney injury - Gabriel, Daniela Ponce [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Martin, Luis Cuadrado [UNESP]; Barretti, Pasqual [UNESP]; Balbi, André Luis [UNESP] (Multimed Inc, 2009)
Background: In some parts of the world, peritoneal dialysis is widely used for renal replacement therapy (RRT) in acute kidney injury (AKI), despite concerns about its inadequacy. It has been replaced in recent years by hemodialysis and, most recently, by continuous venovenous therapies. We performed a prospective study to determine the effect of continuous peritoneal dialysis (CPD), as compared with daily hemodialysis (dHD), on survival among patients with AKI.Methods: A total of 120 patients with acute tubular necrosis (ATN) were assigned to receive CPD or dHD in a tertiary-care university hospital. The primary endpoint was hospital survival rate; renal function recovery and metabolic, acid-base, and fluid controls were secondary endpoints.Results: of the 120 patients, 60 were treated with CPD (G1) and 60 with dHD (G2). The two groups were similar at the start of RRT with respect to age (64.2 +/- 19.8 years vs 62.5 +/- 21.2 years), sex (men: 72% vs 66%), sepsis (42% vs 47%), shock (61% vs 63%), severity of AKI [Acute Tubular Necrosis Individual Severity Score (ATNISS): 0.68 +/- 0.2 vs 0.66 +/- 0.22; Acute Physiology and Chronic Health Evaluation (APACHE) II: 26.9 +/- 8.9 vs 24.1 +/- 8.2], pre-dialysis blood urea nitrogen [BUN (116.4 +/- 33.6 mg/dL vs 112.6 +/- 36.8 mg/dL)], and creatinine (5.85 +/- 1.9 mg/dL vs 5.95 +/- 1.4 mg/dL). In G1, weekly delivered Kt/V was 3.59 +/- 0.61, and in G2, it was 4.76 +/- 0.65 (p < 0.01). The two groups were similar in metabolic and acid-base control (after 4 sessions, BUN < 55 mg/dL: 46 +/- 18.7 mg/dL vs 52 +/- 18.2 mg/dL; pH: 7.41 vs 7.38; bicarbonate: 22.8 +/- 8.9 mEq/L vs 22.2 +/- 7.1 mEq/L). Duration of therapy was longer in G2 (5.5 days vs 7.5 days; p = 0.02). Despite the delivery of different dialysis methods and doses, the survival rate did not differ between the groups (58% in G1 vs 52% in G2), and recovery of renal function was similar (28% vs 26%).Conclusion: High doses of CPD provided appropriate metabolic and pH control, with a rate of survival and recovery of renal function similar to that seen with dHD. Therefore, CPD can be considered an alternative to other forms of RRT in AKI.
Keywords: Acute renal failure; daily hemodialysis